Identification of Hub Genes in Protective Effect of Astragaloside IV on Aconitine-Induced Cardiac Damage in Zebrafish Based on Bioinformatics Analysis - Wang, Mingzhu; Shi, Yanan; Yao, Lei; Li, Qiang; Wang, Youhua; Li, Jianhua; Fu, Deyu (Frontiers in Pharmacology, 2020)
Accumulating evidence suggests that Astragaloside IV (AS-IV) improved cardiac function and protects the cardiovascular system. However, the involved molecular targets are still ambiguous. In this work, we focus on the research that AS-IV can antagonize the arrhythmias and reduce the cardiac damage induced by Aconitine in zebrafish. The zebrafish has advantages in studying the influence of drugs on the cardiovascular disease. The possible mechanisms are further analyzed and hub gene targets are predicted. Firstly, the model of cardiac damage induced by Aconitine is build. Following that, the safe drug concentration of AS-IV is selected and the optimal drug dose was screened within the safe drug concentration. Secondly, we verify the protective effect in cardiovascular system of AS-IV by observing the changes of zebrafish heart rates and cardiac and vascular structure. Thirdly, with aim to demonstrate the antagonistic mechanism of AS-IV heart rates and cardiac damage induced by Aconitine in zebrafish, differentially expressed genes (DEGs) are detected by RNA-seq. Then, the DEGs are further analyzed by bioinformatics such as functional enrichment analysis, protein-protein interaction network and DNA-microRNA network and so on. After that, we predict the hub genes of cardiac protective effects of AS-IV. Finally, we validate these genes in the Gene Expression Omnibus (GEO) database of patients with cardiac damage. Thus, we conclude that miRNA-26b-5p/ATF3/JUN are key targets of AS-IV which plays an important role in maintaining cardiac homeostasis and regulating cardiac remodeling.